2020
DOI: 10.12659/msm.923656
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Short-Segment Fixation versus Long-Segment Fixation for Degenerative Scoliosis with Cobb Angle 20°~40°: A Retrospective Observational Study

Abstract: Background There remains a great deal of controversy regarding the selection of long-segment fixation and short-segment fixation, especially for degenerative scoliosis (DS) patients with Cobb angle 20°~40°. The purpose of this study was to investigate the effects of different fixation levels in DS patients with Cobb angle 20°~40°. Material/Methods We enrolled 96 DS patients, divided into a long-segment fixation group (>3 segments) and a short-segment fixation group (≤3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…For the maintenance of the local kyphosis angle, many scholars also believe that long-segment spinal internal fixation has more advantages. 24,30 Our study showed that LSF was more effective in maintaining spinal stability than SSF at the last follow-up.…”
Section: Efficacy and Safety Of Posterior Short-segment Fixation And ...mentioning
confidence: 54%
“…For the maintenance of the local kyphosis angle, many scholars also believe that long-segment spinal internal fixation has more advantages. 24,30 Our study showed that LSF was more effective in maintaining spinal stability than SSF at the last follow-up.…”
Section: Efficacy and Safety Of Posterior Short-segment Fixation And ...mentioning
confidence: 54%
“…In the view of the principle of treatment of spinal fractures, both the upper and lower two segments of the fractured segment should be fixed to improve the reduction effect on the fracture and to minimize axial rotational motion. However, short fixation can surprisingly provide better stability and clinical efficacy than long fixation according to previous reports [ 30 , 31 ]. The primary role of ULIF is to resist separation of the fractured posterior pelvic ring, which may explain the lack of stability-gaining effect of fixation extending to L4.…”
Section: Discussionmentioning
confidence: 87%
“…12 There is scant evidence of whether short- versus long-segment instrumentation and fixation is preferable in the pediatric population, and a comparative study by Li et al suggest advantages to either approach. 13 For example, short-segment fixation leads to reduced blood loss and shorter intraoperative times, while long-segment instrumentation and fixation provided relief of low back pain and improved spinal-pelvic parameters. 13 A risk-benefit analysis in select pediatric patients should be performed to weigh the increased risk for operative complications to improve objective spinal-pelvic parameters in long-segment instrumentation versus less surgical trauma and the potential for fewer complications in short-segment fixation.…”
Section: Discussionmentioning
confidence: 99%